Politics of marriage in medieval India: Gender and Alliance in Rajasthan - Singh, Sabita (New Delhi Oxford University Press, 2019)
The history of marriage is viewed as social history related to customs and laws, but it is also a reflection of an inner life$1 (Bone that comprises tales of joy, suffering, and the mundane$1 (Bmost of it hidden from the historian$1 (Bs eye. Analysing the institution of marriage in medieval Rajasthan, Singh reconstructs the regional social structures and cultures of the time. The history of Rajasthan has always been romanticized, especially the legends of Sati and Jauhar, both of which along with the rituals related to widowhood are seen as institutional forms of women$1 (Bs oppression. Singh offers a fresh perspective on these customs, often challenging the conventional narrative and unearthing the complex motives behind them. Referring to extensive archival and literary sources, the author delves deep into practices such as polygamy, dowry, and concubinage which are situated in the changing socio-political structures. As the author takes cognizance of the regional variations with respect to cultural norms, what becomes unequivocally clear is the multicultural ethos of India and the fact that history cannot be interpreted in monolithic universal terms.s
Keywords: Social Sector; Costume and Rituals; Wedding and Marriage Costume